Design of a power regulator for photovoltaic power generation - Perera, B.A. Gayan Sugeswara (2016)
Due to the higher population growth and technological advancement, the energy consumption is expected to grow exponentially in next 50 years. Currently the largest portion of global energy demand is fulfilled by fossil fuel that contributes significantly to the global warming and air pollution. The renewable energy resources are attractive alternatives to replace the energy content supplied by the fossil fuels. Solar energy is the driving force for almost all types of renewable energy. The basic components of a solar energy system are DC-DC converter, charge controller, battery pack and inverter.